Environmental problems of fuels with additives - Спиркин, В.Г.; Ткачев, И.И.; Тарарышкин, П.А. (Proceedings of National Aviation University (archive), 2009)
In the article the ecological problems of application of fuels are considered with additives. The results of research of influence of row of additives are presented on oilings properties of oils.